2013
DOI: 10.1111/jpi.12098
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin enhances chondrogenic differentiation of human mesenchymal stem cells

Abstract: Intramembranous ossification and endochondral ossification are two ways through which bone formation and fracture healing occur. Accumulating amounts of evidence suggests that melatonin affects osteoblast differentiation, but little is known about the effects of melatonin on the process of chondrogenic differentiation. In this study, the effects of melatonin on human mesenchymal stem cells (MSCs) undergoing chondrogenic differentiation were investigated. Cells were induced along chondrogenic differentiation vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 44 publications
4
68
0
1
Order By: Relevance
“…Melatonin has confirmed to increase glycosaminoglycan synthesis and cartilage tissue, as well as to enhance the expression of chondrogenic marker genes including aggrecan, collagen type II and X, SOX9, and BMP2 during the chondrogenic differentiation at least partially through melatonin receptors (MT) including MT1 and MT2 55 . Meanwhile, it has been reported that Osterix regulates chondrocyte differentiation and bone growth in growth plate chondrocytes during endochondral ossification 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has confirmed to increase glycosaminoglycan synthesis and cartilage tissue, as well as to enhance the expression of chondrogenic marker genes including aggrecan, collagen type II and X, SOX9, and BMP2 during the chondrogenic differentiation at least partially through melatonin receptors (MT) including MT1 and MT2 55 . Meanwhile, it has been reported that Osterix regulates chondrocyte differentiation and bone growth in growth plate chondrocytes during endochondral ossification 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a highly evolutionarily conserved molecule with multiple biological functions, such as regulation of circadian rhythms, inhibition of tumor growth, immunomodulation, and antioxidation . In addition, melatonin plays a vital role in regulating skeleton formation and development and has been well established to promote both osteogenic and chondrogenic differentiations of MSCs . During in vitro osteogenic differentiation of MSCs, melatonin treatment dramatically stimulated osteogenic differentiation and increased expressions of osteogenic markers .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown evidences that melatonin can enhance the production of iPSCs due to its antioxidant activity [8, 9]. In human adult MSCs, for instance, melatonin combined with the extracellular matrix can enhance cellular alkaline phosphatase (AP) activity, induce osteogenesis via the melatonin receptor 2 (MT2), and also reverse stress-induced MSC injuries [1013]. Meanwhile, melatonin can elevate the viability of rat neural stem cells (NSCs) and induce NSCs differentiate into dopaminergic neurons and decrease astrocyte production [14, 15].…”
Section: Introductionmentioning
confidence: 99%